Aural History. - Ashtor, Gila (Punctum Books, 2020)
Aural History is an anti-memoir memoir of encountering devastating grief that uses experimental storytelling to recreate the winding, fractured path of loss and transformation. Written by a thirty-something psychotherapist and queer theorist, Aural History is structured as a sequence of three sections that each use different narrative styles to represent a distinctive stage in the protagonist's evolving relationship to trauma. Aural History explores how a cascade of self-dissolving losses crisscrosses a girl's coming of age. Through lyric prose, the first section follows a precocious tomboy whose fierce attachment to her father forces her, when he dies and she is twelve years old, to run the family bakery business, raise a delinquent younger brother, and take care of a destructive, volatile mother. In part two, scenes narrated in the third person illustrate a high-achieving high school student who is articulate and in control except for bouts of sudden and inchoate attractions, the first of which is to her severe and coaxing English teacher. The third story tells of her relation with a riveting, world-famous professor, interspersed with a tragic-comic series of dialogues between the protagonist and a cast of diverse psychotherapists as she, now twenty-five years old and living in New York City, undertakes an odyssey to understand why true self-knowledge remains elusive and her real feelings, choked and incomplete. In what Phillip Lopate calls "an amazing document," Aural History pushes the narrative conventions of memoir to capture a story the genre of memoir usually struggles to tell: that you can lose yourself, and have no way to know it